A probe-fed U-shaped cross-sectional antenna with tuning stubs on a U-shaped ground plane - Srimoon, Duang Arthit; Phongcharoenpanich, Chuwong; Krairiksh, Monai (My University, 2006)
A probe-fed U-shaped cross-sectional antenna with tuning stubs on a U-shaped ground plane is proposed for wideband applications. The bottom of the antenna is etched to form tuning stubs for impedance matching. The simulated results of return loss, co- and cross-polarized patterns are presented and compared with the measured ones. Characteristics of a constructed antenna prototype at the operating frequency show that the antenna has an impedance bandwidth (2:1 VSWR) of 37.44% and average gain level of 8.5 dBi. Good radiation characteristics of the proposed antenna have been obtained that is the cross-polarization level and front-to-back ratio in both E- and H-planes across the large bandwidth are better than 22 dB and 12 dB, respectively. Copyright © 2006 The Institute of Electronics, Information and Communication Engineers.
Keywords: Broadband; Finite-difference time-domain; Polarization; Tuning stubs; U-shaped cross-sectional antenna; U-shaped ground plane